Competition in a Dual Economy. - Bowring, Joseph (Princeton legacy library., 2014)
Joseph Bowring places the dual economy in a historical context and analyzes the evolution of core and periphery competition. He also refines the dual economy hypothesis and provides strong new empirical support for it. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal.